2018
DOI: 10.1002/jts.22291
|View full text |Cite
|
Sign up to set email alerts
|

Adults with Comorbid Posttraumatic Stress Disorder, Alcohol Use Disorder, and Opioid Use Disorder: The Effectiveness of Modified Prolonged Exposure

Abstract: Opioid use disorders (OUDs) are a growing problem in the United States. When OUDs co-occur with problematic drinking and posttraumatic stress disorder (PTSD), negative drug-related mental and physical health outcomes may be exacerbated. Thus, it is important to establish whether PTSD treatments with established efficacy for dually diagnosed individuals also demonstrate efficacy in individuals who engage in problematic drinking and concurrent opioid misuse. Adults who met DSM-IV-TR criteria for PTSD and alcohol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 44 publications
4
8
0
Order By: Relevance
“…Reductions in SUD observed in the current study were similar to findings from previous studies of COPE in civilians (Mills et al, 2012;Ruglass et al, 2017) and comparable to findings observed in randomized controlled trials of SUD-only patients (Anton et al, 2006;Dutra et al, 2008). The findings from this study converge with those of previous investigations (Coffey et al, 2006;Foa et al, 2013;Mills et al, 2012;Norman et al, 2016;Peck et al, 2018;Persson et al, 2017;Ruglass et al, 2017) and show that PE delivered in the context of an integrated or comprehensive SUD treatment is beneficial, even among individuals who continue to use substances. The findings also highlight that there is room for improvement, particularly with regard to SUD outcomes, and suggest that the addition of pharmacotherapies or other interventions to further reduce craving and substance use may be benefit some patients with SUD/PTSD.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Reductions in SUD observed in the current study were similar to findings from previous studies of COPE in civilians (Mills et al, 2012;Ruglass et al, 2017) and comparable to findings observed in randomized controlled trials of SUD-only patients (Anton et al, 2006;Dutra et al, 2008). The findings from this study converge with those of previous investigations (Coffey et al, 2006;Foa et al, 2013;Mills et al, 2012;Norman et al, 2016;Peck et al, 2018;Persson et al, 2017;Ruglass et al, 2017) and show that PE delivered in the context of an integrated or comprehensive SUD treatment is beneficial, even among individuals who continue to use substances. The findings also highlight that there is room for improvement, particularly with regard to SUD outcomes, and suggest that the addition of pharmacotherapies or other interventions to further reduce craving and substance use may be benefit some patients with SUD/PTSD.…”
Section: Discussionsupporting
confidence: 91%
“…The majority of available COPE sessions (73.7%) and RP sessions (61.7%) were attended. Completion rates and attendance in this study were similar to or higher than previous studies of non-exposure based, integrated treatments (Hien et al, 2009;Myers, Browne, & Norman, 2015;Najavits et al, 2018) as well as exposure-based, integrated treatments (Coffey et al, 2016;Foa et al, 2013;Mills et al, 2012;Peck et al, 2018;Ruglass et al, 2017;Schacht et al, 2017). Improvements in retention observed in the current study may be due, in part, to modifications made to the treatment protocol.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Finally, prior medical research suggests that the risk of opioid abuse may be exacerbated by PTSD (Peck et al 2018). We empirically confirm this suggestion in Appendix Table 6, where we show that PTSD substantially increases the adverse effects of combat.…”
Section: Mechanismssupporting
confidence: 78%
“…A parallel area of study has examined the connections between OUD and MHCs, which has similarly revealed substantial overlap among these conditions. Depression, anxiety and ASPD rank among the most commonly observed (Santo et al , 2022), but there is also evidence suggesting post-traumatic stress disorder (PTSD) may be more common among people diagnosed with OUD relative to those who do not have a similar condition (Peck et al , 2018).…”
Section: Introductionmentioning
confidence: 99%